Influence of late-Holocene climate change on the solid-phase speciation and long-term stability of arsenic in sub-Arctic lake sediments - Clare Miller; Parsons, MB; Jamieson, HE; Ardakani, OH; Gregory, BRB; Galloway, JM (2020)
Sediment cores were collected from two lakes in the Courageous Lake Greenstone Belt (CLGB), central Northwest Territories, Canada, to examine the influence of late-Holocene warming on the transport and fate of arsenic (As) in sub-Arctic lakes. In both lakes, allochthonous As-bearing minerals ( i.e. arsenopyrite and scorodite) were identified in sediment deposited during times of both regional warming and cooling, suggesting that weathering of bedrock and derived surficial materials provides a continual source of As to lakes of the CLGB. However, maximum porewater As (84 μg·L −1 and 15 μg·L −1 ) and reactive organic matter (OM; aquatic and terrestrial-derived) concentrations in each lake are coincident with known periods of regional climate warming. It is inferred that increased biological production in surface waters and influx of terrigenous OM led to the release of sedimentary As to porewater through reductive dissolution of As-bearing Fe-(oxy)hydroxides and scorodite during episodes of regional warming. Elevated sedimentary As concentrations (median: 36 mg·kg −1 range: 29 to 49 mg·kg −1 ) are observed in sediment coeval with the Holocene Thermal Maximum (ca. 5430 ± 110 to 4070 ± 130 cal. years BP); at these depths, authigenic As-bearing framboidal pyrite is the primary host of As in sediment and the influence of organic matter on the precipitation of As-bearing framboidal pyrite is apparent petrographically. These findings suggest that increased biological productivity and weathering of terrestrial OM associated with climate warming influences redox cycles in the near-surface sediment and enhances the mobility of As in northern lakes. Knowledge generated from this study is relevant for predicting future climate change-driven variations in metal(loid) cycling in aquatic systems and can be used to interpret trends in long-term environmental monitoring data at historical, modern, and future metal mines in northern environments.